2022
DOI: 10.1096/fj.202101649rrr
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular aspects of the (pro)renin receptor: Function and significance

Abstract: Cardiovascular diseases (CVDs), including all types of disorders related to the heart or blood vessels, are the major public health problems and the leading causes of mortality globally. (Pro)renin receptor (PRR), a single transmembrane protein, is present in cardiomyocytes, vascular smooth muscle cells, and endothelial cells. PRR plays an essential role in cardiovascular homeostasis by regulating the renin‐angiotensin system and several intracellular signals such as mitogen‐activated protein kinase signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 169 publications
(492 reference statements)
0
7
0
Order By: Relevance
“…Changes in podocyte structure and function are related to glomerular filtration barrier pathology, and currently become the diagnostic target of glomerular lesions [ 14 ]. Endothelial injury can lead to the development of kidney disease and cardiovascular disease in patients with diabetes and hypertension [ 28 , 29 ], Progress of endothelial injury is mainly due to GCX degradation, which leads to proteinuria and kidney damage. We then measured the levels of Syndecan-1 and HS in the serum of rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in podocyte structure and function are related to glomerular filtration barrier pathology, and currently become the diagnostic target of glomerular lesions [ 14 ]. Endothelial injury can lead to the development of kidney disease and cardiovascular disease in patients with diabetes and hypertension [ 28 , 29 ], Progress of endothelial injury is mainly due to GCX degradation, which leads to proteinuria and kidney damage. We then measured the levels of Syndecan-1 and HS in the serum of rats.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, spinal anesthesia, including epidural anesthesia and spinal anesthesia, may have a role to play in reducing renal injury. Inhalation anesthetics such as sevoflurane and enflurane have protective effects on the kidney [ 29 ]. Animal experiments have confirmed that propofol can reduce markers of oxidative stress in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial dysfunction can occur by the activation of PRR and resultant high Ang II activity [ 44 ]. Renin may interact with PRR to be of relevance in CVD in many ways [ 45 ], covering the enhancement of the RAS by catalyzing Ang I production [ 46 ], activation of mitogen-activated protein kinase (MAPK) signaling pathways [ 47 ], association with V-ATPase implicating a non-RAS-related function [ 48 ], and regulation of the Wnt/β-catenin pathway [ 49 ]. As reviewed elsewhere, activation of PRR in cardiomyocytes may contribute to myocardial ischemia/reperfusion injury, cardiac hypertrophy, diabetic cardiomyopathy, salt-induced cardiac damage, and heart failure [ 49 ].…”
Section: Ckm Syndrome Is Causal Of Ras Perturbationmentioning
confidence: 99%
“…Some studies have implicated prorenin in the pathogenesis of diseases such as diabetes and hypertension, [3][4][5][6] whereas others have rebuked that its effects are merely through enhancement of the RAAS. 7 Although several studies have investigated the role of prorenin on the vascular system and in hypertension, [8][9][10] none have determined the direct effect of prorenin on arterial contractility. In this study, we aimed to establish whether prorenin could alter arterial contractility, which could have an impact on hypertension.…”
Section: Introductionmentioning
confidence: 99%